1997
DOI: 10.1038/sj.onc.1200997
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ras and retinoic acid on nerve growth factor induction of transin gene expression in PC12 cells

Abstract: Nerve growth factor (NGF)-and ras-induced neuronal di erentiation of PC12 cells is accompanied by expression of transin, a secreted metalloproteinase. Retinoic acid (RA) is known to exert important e ects on neural cell proliferation and di erentiation. In this study we have analysed di erent PC12 sublines which express either activated Ras or dominant negative p21 N17 Ras, to evaluate the in¯uence of retinoic acid (RA) on the response of the transin gene to NGF and Ras. There was a good correlation between ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…6, incubation with the glucocorticoid, which strongly increased RARβ2 promoter activity, caused a much weaker activation of the DR5‐TK construct. Furthermore, the activity of the RSV promoter which, in agreement with previous results from our laboratory, was specifically induced by Ras Val12 (Cosgaya et al . 1997a) was unaffected by RA.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6, incubation with the glucocorticoid, which strongly increased RARβ2 promoter activity, caused a much weaker activation of the DR5‐TK construct. Furthermore, the activity of the RSV promoter which, in agreement with previous results from our laboratory, was specifically induced by Ras Val12 (Cosgaya et al . 1997a) was unaffected by RA.…”
Section: Resultssupporting
confidence: 91%
“…1996). In addition, RA causes a transient expression of the low affinity neurotrophin receptor p75 NTR , tyrosine hydroxilase and TGF‐β1 genes similar to that observed during NGF‐induced differentiation (Cosgaya and Aranda 1996; Cosgaya et al . 1997b).…”
Section: Discussionmentioning
confidence: 62%
“…RA-induced neuronal differentiation is characterized by the expression of tissue-specific genes, proteins, ion channels, and receptors in a developmentally controlled manner (Guan et al, 2001). Although we have previously shown that RA inhibits PC12 cell proliferation and mimics the effect of neurotrophins on the expression of several genes, the retinoid does not cause neurite extension and does not increase the levels of early response genes such as c-fos in parental PC12 cells (Cosgaya et al, 1996(Cosgaya et al, , 1997a(Cosgaya et al, , 1997b(Cosgaya et al, , 1998. In contrast, RA can stimulate the differentiation of some PC12 cell subclones.…”
Section: Introductionmentioning
confidence: 83%
“…Cell 10.1091/ mbc.E04 -05-0439. Article and publication date are available at www.molbiolcell.org/cgi/doi/10.1091/mbc.E04 -05-0439. c-fos in parental PC12 cells (Cosgaya et al, 1996(Cosgaya et al, , 1997a(Cosgaya et al, , 1997b(Cosgaya et al, , 1998. In contrast, RA can stimulate the differentiation of some PC12 cell subclones.…”
Section: Introductionmentioning
confidence: 99%
“…Because microarray analysis may miss changes in gene expression when genes are expressed at low levels, we asked whether genes that are involved in cell adhesion and that are regulated by Ras and oncogenic ETS factors were repressed by TEL (73). MMPs are stimulated by Ras through the activation of ETS and AP-1 factors and repressed by negatively acting ETS factors such as Erg (15,16,29,33,59,80). RNA blot analysis indicated that the levels of the MMPs expressed in NIH 3T3 cells, including MMP1, MMP7, and MMP9, were low in these cells and were not affected by TEL (data not shown).…”
Section: Resultsmentioning
confidence: 99%